Dialektika Metodologi Ekonomi Islam: Analisis Komparatif Pemikiran Umer Chapra dan Muhammad Baqir As-Sadr - Nuranisya, Siti (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This research aims to conduct a comparative analysis of the dialectics of Islamic economic methodology between two prominent figures: Umer Chapra and Muhammad Baqir as-Sadr. Umer Chapra represents the Mainstream School, which tends to be evolutionary by integrating moral values into the modern economic framework. Conversely, Muhammad Baqir as-Sadr, through the Iqtishaduna School, offers a revolutionary-doctrinal approach that demands the total independence of Islamic economics from the capitalist system. Utilizing a descriptive-comparative library research method, this study finds that their fundamental differences lie in the epistemological aspects, particularly regarding the concept of resource scarcity and the moral filter mechanism. Despite their differing methodological strategies, both scholars converge on the vision of distributive justice and social welfare. The results of this analysis are expected to strengthen the theoretical foundation in developing Sharia Economic Law that is adaptive yet consistently upholds substantive Sharia principles.